Pengaruh Dividend Initiations dan Dividend Cut/Omissions terhadap Return Saham di Bursa Efek Jakarta - Sri Dwi Ari Ambarwati (Jurnal Siasat Bisnis, 2005)
This research investigates market reactions to initiations and cut/omissions of cash dividend payment. Consistent with prior literature, the result of this research tend to support the propositions that shareholders make considerable use of the information implicit in dividend announcement. Shareholders react positively significant to the dividend initiations announcement and negatively significant to the dividend cut/omissions announcement. A multiple regression model is formulated to identify the factors that contribute significantly to the capital gain (loss) suffered by shareholders when firm decide to initiate (cut/omit) dividend. Result indicate that, in conformity with the information content hypothesis, the shareholders’s respond to dividend initiations significantly depends on  the firm size and the cumulative return movement (CARM) in the preceding period. Whereas, the shareholders’s re¬spond to dividend cut/omissions significantly depends on the cumulative return movement (CARM) in the preced¬ing period and risk/corrected beta of the firm at alpha 1% and 5%.Keywords: Signaling hypothesis, Dividend initiations, dividend cut/omissions